2014 IEEE International Energy Conference (ENERGYCON) 2014
DOI: 10.1109/energycon.2014.6850566
|View full text |Cite
|
Sign up to set email alerts
|

A centralised DC power supply solution for LED lighting networks

Abstract: In the context of the FP7 CIP-ICT Programme, the EDISON project 1 has the ambitious goal to introduce a new way of thinking lighting networks in buildings, for both retrofitting actions and new constructions. It proposes an innovative ICT-based solution for lighting infrastructure that aims to improve power efficiency, reduce CO 2 emissions and encourage the use of small-scale renewable energy sources in public and private buildings. In particular, this paper focuses on a relevant aspect of the EDISON solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…As such, a choice can be made between LVAC or LVDC in the planning of the local electrical grid. Some studies have shown that a centralized rectification can be beneficial for DC loads (such as LED lighting) [5]- [7]. However, to the best knowledge of the authors, a systematic approach and tool for this choice does not exist.…”
Section: Introductionmentioning
confidence: 99%
“…As such, a choice can be made between LVAC or LVDC in the planning of the local electrical grid. Some studies have shown that a centralized rectification can be beneficial for DC loads (such as LED lighting) [5]- [7]. However, to the best knowledge of the authors, a systematic approach and tool for this choice does not exist.…”
Section: Introductionmentioning
confidence: 99%
“…The paper discusses the different solutions for integrating an intelligent control system in the lighting infrastructure to be able to automatically dim or switch on or off the lamps based on user presence (or user's preferences) and on the availability of daylight scavenging. While presenting the flexibility of DC-based lighting solutions, the paper clearly motivates the design choices taken for the EDISON project [6][7][8] and introduces the main building blocks of the EDISON smart lighting system. It also introduces the latest efforts to make the EDISON smart lighting solutions interoperate with other (building management) systems.…”
Section: Introductionmentioning
confidence: 99%
“…In this program, in the street lamp control cabinet equipped with AC/DC power supply, the AC power conversion to DC 240V, and the distribution line output to the LED lamp; in the street with high reliability DC/DC drive power instead of the original AC/DC drive power supply. DC power supply centralized layout, which will help improve the efficiency of power conversion, and simplify the LED street lamp drive power, and DC power supply voltage stability, to avoid the impact of LED lamps, LED lamps will help improve the life of the lamp drive power supply life and reliability, Maintenance cycle, reduce maintenance costs; AC and DC power conversion part of the DC installed in the road control cabinet, to avoid the maintenance of the pole, is conducive to reducing maintenance workload [3].…”
Section: Introductionmentioning
confidence: 99%